Ten‐color 15‐antibody flow cytometry panel for immunophenotyping of lymphocyte population. (May 2017) - Rajab, A.; Axler, O.; Leung, J.; Wozniak, M.; Porwit, A.
Summary: We have developed a lymphoproliferative disorder screening tube (LPD‐ST) with the aim to provide comprehensive immunophenotyping of lymphocyte subsets with minimal need for additional testing. The LPD‐ST consists of CD4/kappa FITC, CD8/lambda PE, CD3/CD14ECD, CD38PC5.5, CD20/CD56PC7, CD10APC, CD19APC‐A700, CD5APC‐A750, CD57/CD23PB and CD45KO. The LPD‐ST was validated against previously used lymphocyte subset panels in Canada (n=60) and in Sweden (n=43) and against the OneFlow ™ LST (n=60). The LPD‐ST panel was then implemented in clinical practice using dried monoclonal antibody reagents (Duraclone ® ) on 649 patient samples in Sweden. In 204 of 649 samples (31%), a monotypic B‐cell population was found. Of these cases, a final diagnosis could be rendered in 106 cases (52%), and in the remainder, additional B‐cell immunophenotyping was performed. In 20 (3%) samples, an aberrant T‐cell population was confirmed by additional testing. Of 425 samples diagnosed as normal/reactive lymphoid tissue, 50 (12%) required additional immunophenotyping, mostly due to an abnormal CD4/CD8 ratio. The LPD‐ST tube significantly minimizes the need for additional testing, improves the turn‐around time, and reduces the cost of LPD immunophenotyping. It is also suitable for investigating paucicellular samples such as cerebrospinal fluid or fine needle aspirates.